تحليل الواقع المالي وتطوره في بنك جيهان للاستثمار والتمويل الإسلامي للمدة "2021-2011" - عبدالله، ياسين عثمان (جامعة الموصل - كلية الإدارة والاقتصاد, 2022)
يعتبر البنك من المؤسسات الاقتصادية المهمة في تحريك الأنشطة الاقتصادية لأي بلد ويمثل ركنا رئيسا من أركان إحداث التغيرات في التنمية الاقتصادية في المجتمعات الآن. لذلك يقوم البحث بتحليل الواقع المالي وتطوره في بنك جيهان للاستثمار والتمويل خلال المدة (2011-2021). وتتجلى أهمية هذا البحث في تشخيص أداء البنك في تعبئة الموارد المالية وقدرتها في توجيهها إلى الأغراض التي تخدم تحريك النشاطات الاقتصادية. وافترض هذا البحث أن هناك قدرة للبنك على تعبئة المدخرات وزيادة أرصدة البنك النقدية وتوظيفها بشكل جيد خدمة لتحقيق الأرباح الاقتصادية. وقد تم التوصل إلى مجموعة من الاستنتاجات من، أهمها إن هناك تطورا في إجمالي الموجودات والنقد في الصندوق خلال مدة البحث، وكذلك تم استنتاج بأن هناك ارتفاعا في إيرادات التمويل والاستثمارات، حيث بلغ معدل النمو المركب لمدة البحث (19.8%)، وارتفاع في صافي الأرباح بعد الضريبة، إذ بلغ معدل النمو المركب (8.86%). وأخرا اقتراح البحث مجموعة من اقتراحات لعل أهمها تشجيع أفراد المجتمع على إيداع مدخراتهم في البنوك. The Bank is considered one of the important economic institutions in stimulating the economic activities of any country and represents a major pillar of bringing about changes in economic development in societies now. Therefore, the research analyzes the financial reality and its development in Cihan Bank for Investment and Finance during the period (2011-2021). The importance of this research is manifested in diagnosing the bank's performance in mobilizing financial resources and its ability to direct them to the purposes that serve to stimulate economic activities. This research assumed that the bank can mobilize savings and increase the bank's cash balances and use it well to achieve economic profits. The conclusion was reached that there was a development in the total assets and cash in the fund during the research period, and also it was concluded that there was a rise in financing and investment revenues, as the compound growth rate for the research period reached (19.8%), and an increase in net profits after tax, as it reached Compound growth rate (8.86%). Finally, the research suggested a set of suggestions, perhaps the most important of which is to encourage community members to deposit their savings in banks.
Keywords: المؤسسات الاقتصادية -- التمويل الإسلامي -- التنمية الاقتصادية -- الموارد المالية